Searches for ALPs with Current and Future X-ray Satellites - Perimeter Institute (Perimeter Institute, 2017)
Galaxy clusters represent excellent laboratories to search for Axion-Like Particles (ALPs). They contain magnetic fields which can induce quasi-sinusoidal oscillations in the X-ray spectra of AGNs situated in or behind them. Ultra-deep Chandra observations of the Perseus cluster contain over 5 x 105 counts from the central NGC1275 AGN, and represent an extraordinary dataset for ALP searches. In this talk I will describe how we used these to search for spectral irregularities from the AGN. No irregularities were found at the ~30% level, allowing us to place leading constraints on the ALP-photon mixing parameter gaγγ  <1.5 × 10−12GeV−1 for ma < 10-12 eV. I will move on to discuss the upcoming Athena X-ray Observatory, due for launch in 2028. The X-ray Integral Field Unit (X-IFU) instrument onboard will be far better able to constrain ALPs than Chandra, due to its excellent energy resolution. Using the SIXTE simulation software, we estimate that non-observation of spectral modulations for a 200ks observation of NGC1275 will constrain gaγγ  <1.5 × 10−13GeV−1 , an order of magnitude improvement over that derived from Chandra data.
Keywords: Particle Physics